Catalytic transfer hydrogenation of oleic acid to octadecanol over magnetic recoverable cobalt catalysts. Issue 2 (18th December 2018) - Wang, Juncheng; Nie, Renfeng; Xu, Ling; Lyu, Xilei; Lu, Xiuyang
Abstract : Earth-abundant magnetic cobalt is highly efficient for CTH of oleic acid with isopropanol as a hydrogen donor, affording 100% conversion as well as 91.9% octadecanol yield at 200 °C, which can be ascribed to the synergistic effect between Co δ + and Co 0 . Abstract : Efficient transformation of biomass into fuel and chemicals under mild conditions with cost-effective and environmentally friendly characters is highly desirable but still challenging. Herein, a scalable and Earth-abundant cobalt catalyst was used for selective catalytic transfer hydrogenation (CTH) of unsaturated fatty acids to fatty alcohols with sustainable isopropanol as a hydrogen donor. By tuning the surface Co composition by varying the reduction temperature, the catalytic performance could be easily boosted. At 200 °C in 4 h, the optimal catalyst Co-350 (reduced at 350 °C) gives 100% oleic acid conversion with 91.9% octadecanol selectivity. Various characterization studies reveal that the co-existence of Co δ + and Co 0 over the cobalt core might be responsible for its high performance for CTH of oleic acid. This catalyst could be magnetically separated and is highly stable for reusing ten times. Moreover, this cobalt catalyst is relatively cheap and easy to scale-up, thus achieving a low-cost transformation of biomass into high value-added chemicals.